Attenuation of quorum sensing regulated virulence and biofilm development in Pseudomonas aeruginosa PAO1 by Diaporthe phaseolorum SSP12. (May 2018) - Pattnaik, Subha Swaraj; Ranganathan, SampathKumar; Ampasala, Dinakara Rao; Syed, Asad; Ameen, Fuad; Busi, Siddhardha
Abstract: In recent years, Pseudomonas aeruginosa PAO1 emerged as the significant pathogenic microorganism in majority of the hospital-acquired infections due to its resistance to the conventional antibiotics by virtue of its highly organized quorum sensing and associated biofilm formation. In the present study, quorum sensing attenuation potential of Diaporthe phaseolorum SSP12 extract was investigated against P. aeruginosa PAO1 amply supported by molecular docking studies. D. phaseolorum SSP12 extract significantly inhibited the production of LasI/R mediated LasA protease, LasB elastase and chitinase with 66.52 ± 5.41, 71.26 ± 4.58 and 61.16 ± 4.28% of inhibition respectively at a concentration of 750 μg mL −1 . In addition, RhlI/R mediated production of pyocyanin, exopolysaccharides and rhamnolipids were also down-regulated by 74.71 ± 3.97, 66.41 ± 3.62 and 63.75 ± 3.76% respectively on treatment with sub-MIC concentration of D. phaseolorum SSP12. The light, fluorescence and confocal laser scanning microscopic (CLSM) analysis confirmed the significant disruption in biofilm formation. The presence of bioactive constituents such as phenyl ethylalcohol, 2, 4-di- tert -butylphenol, fenaclon, 1, 4-phenylenediacetic acid, and benzyl hydrazine in D. phaseolorum SSP12 extract was evident from Gas chromatography-mass spectrophotometric (GC-MS) analysis. From the in silico molecular docking studies, fenaclon and 2, 4-di- tert -butylphenol competitively binds to QS receptors LasR and RhlR and alters the binding of its cognate ligands and modulates the expression of virulence phenotypes. The promising anti quorum sensing efficacy of D. phaseolorum SSP12 extract suggested new avenues for development of anti-infective drugs from fungal derived metabolites to counteract the problems associated with conventional antibiotic therapies. Graphical abstract: Highlights: Anti quorum sensing potential of D. phaseolorum SSP12 extract against P. aeruginosa PAO1 was evaluated. Anti biofilm efficacy of D. phaseolorum SSP12 extract was determined against P. aeruginosa PAO1. CLSM analysis corroborated the biofilm inhibition potential of crude fungal extract. GC-MS anlalysis confirmed the presence of bioactive metabolites responsible for quorum sensing attenuation. In silico molecular docking studies give an insight into the mechanism of action of quorum sensing attenuation.